The Complexities of Researching Youth Civic Engagement in Canada with/by Indigenous Youth: Settler-colonial challenges for Tikkun Olam—Pedagogies of repair and reconciliation - Korteweg, Lisa; Bissell, Alex (Canadian Society for Study of Education (CSSE), 2016)
We discuss the first stage of our Tikkun research study that focuses on an indigenized approach to youth participatory action research in a northern Ontario context. Our research design began with an Indigenous youth-generated report, the Feathers of Hope (FoH): A First Nations Youth Action Plan (2014), highlighting the needs of Indigenous youth in their own words and experiences. Readings of the report has led to deep theorizing on questions of a university-based research model for indigenized youth participatory action research (I-YPAR) as well as our ongoing deep ethical dilemmas of settler researchers co-collaborating on research by/with Indigenous youth. We raise these issues as we theorize the possibilities and complexities of a pedagogy of repair and reconciliation (tikkun olam) during our reflexive dialogues as settler-researchers and with Indigenous youth.